Biodegradable Copper‐Based Nanoparticles Augmented Chemodynamic Therapy through Deep Penetration and Suppressing Antioxidant Activity in Tumors. Issue 14 (2nd June 2021) - Zheng, Runxiao; Cheng, Yan; Qi, Fan; Wu, Yunyun; Han, Xiaoqing; Yan, Jiao; Zhang, Haiyuan
Abstract: Chemodynamic therapy (CDT) efficacy has been limited by the poor penetration ability of large nanoparticles (NPs) and the antioxidant activity of tumors, especially high heme oxygenase (HO‐1) and glutathione (GSH) levels. Herein, PEGylated CuMoO x ‐coated and zinc protoporphyrin IX (ZP)‐loaded Cu (CCMZ) NPs are designed to afford rapid degradation ability and augmented CDT efficacy through inhibiting HO‐1 activity and depleting GSH. The deep penetration of tumor can be achieved under the high levels of GSH, which triggers the degradation of CuMoO x shell. Meanwhile, GSH itself is depleted, which converts the reductive environment into constant oxidative environment, thus leading to the degradation of Cu core. Furthermore, the release of ZP from CCMZ NPs can inhibit HO‐1 activity and provide a favorable microenvironment for CDT, and the release of Cu and Mo ions can convert hydrogen peroxide into hydroxyl radical to eliminate tumor cells more efficiently. In addition, CCMZ NPs also play an immune vaccine‐like effect to recruit different immune cells for antitumor immunotherapy. In vitro and in vivo studies prove the augmented CDT property of CCMZ NPs, supplying a new strategy for improving CDT efficacy. Abstract : CuMoO x ‐coated and zinc protoporphyrin IX (ZP)‐loaded Cu (CCMZ) nanoparticles (NPs) are designed for chemodynamic therapy, which can be rapidly degraded in the presence of glutathione and penetrate into deep tumors. The biodegradation also triggers the release of ZP and Cu ions, which can simultaneously inhibit heme oxygenase‐1 activity and deplete glutathione, leading to augmented chemodynamic therapy.